BUILDING A FARM TEAM IN A DOWN ECONOMY. - Herrenkohl, Eric (Public Management (00333611), 2010)
The article offers information on the benefits of building a farm team during low economic times. It mentions that interviewing and networking during bad economies can be beneficial which include getting good performers who shake loose and are available during bad times, interviewing but not necessarily hiring, and building a network to build relationships. It adds that a regular schedule of interviews can keep employers apprised of the trend in the marketplace.